An application of two non-parametric techniques to the prices of British dwellings: An examination of cyclicality. (August 2018) - Gray, David
Using a Pesaran-Timmermann test of co-movement, Cook and Watson (Cook S and Watson D, 2015, A new perspective on the ripple effect in the UK housing market: Co-movement, cyclical subsamples and alternative indices. Urban Studies 53(14): 3048–3062) suggest they have highlighted the 'ripple' effect. Using reference series of the UK, London, Scotland and three deterministic-periodic series, regional prices are shown to have similar cyclical characteristics, with delays based on distance from London. With periodicities consistent with those revealed by spectral analysis, the deterministic-periodic series reference provides a means of establishing cyclical characteristics whilst avoiding issues concerning variable amplitudes. Although a ripple is revealed, using London as a reference poses problems empirically: its cycle is likely to be atypical as well as asynchronised.